MAKNA RAGAM HIAS PADA RANA MAKAM RAJA RAJA SUMENEP DI ASTA TINGGI MADURA - Tulistyantoro, Lintu
Cultural Study to cultural physical aspect is a study emphasizing its space and time context. The context of space explain where the object is. The context of time emphasizing the situation and circumstance that happened at a period when the object created. Studies to cultural physical aspects, such as the aspect of mind and behavior, are important element in discovering the meaning of such an object. The physical aspects are expression from the perpetrators thoughts and well- established behaviour of the society. Ornament Style at Rana in the Mausoleum of Sumenep Kings have specific forms is compared to ones which exist in other areas in Madura. The rectangular forms with varied ornament are the uniqueness of such a Rana. Primordial, Hindu-Budhism, Chinese ornament, in function context of Islam tombs, can present harmony in such a tomb. Each cultural presented in their own manner without having reductions. This condition generates an interesting object to be studied, because cultural differences, but in harmony produced one interesting design entity. Similarity between these cultures, and open minded characters of Ladang-Maritim society, the wisdom of Islamic Sufism that grew at that time made it possible for an adaptation to the values of the ages. These Ornaments become interesting because meaning cannot be separated from the Rana\'s structure themselves, where initial structures are the medium between the world above and the underworld. This mediums is important in Madura society\'s relegion life. So, Ornaments have a Similar value, which is an image of the world above and the underworld.